A pilot study investigating the effects of fast left prefrontal rTMS on chronic neuropathic pain - Borckardt, Jeffrey J. (2009)
OBJECTIVE: Stimulating the human cortex using transcranial magnetic stimulation (TMS) temporarily reduces clinical and experimental pain, however, it is unclear which cortical targets are the most effective. The motor cortex has been a popular target for managing neuropathic pain, while the prefrontal cortex has been investigated for an array of nociceptive pain conditions. It is unclear whether the motor cortex is the only effective cortical target for managing neuropathic pain, and no published studies to date have investigated the effects of prefrontal stimulation on neuropathic pain. DESIGN: This preliminary pilot trial employed a sham-controlled, within-subject, cross-over design to evaluate clinical pain as well as laboratory pain thresholds among four patients with chronic neuropathic pain. Each participant underwent three real and three sham 20-minute sessions of 10Hz left prefrontal rTMS. Daily pain diaries were collected for 3-weeks before and after each treatment phase along with a battery of self-report pain and mood questionnaires. RESULTS: Time-series analysis at the individual patient level indicated that real TMS was associated with significant improvements in average daily pain in 3 of the 4 participants. These effects were independent of changes in mood in 2 of the participants. At the group level, a decrease of 19% in daily pain on average, pain at its worst, and pain at its least was observed while controlling for changes in mood, activity-level and sleep. The effects of real TMS were significantly greater than sham. Real TMS was associated with increases in thermal and mechanical pain thresholds whereas sham was not. No statistically significant effects were observed across the questionnaire data. CONCLUSIONS: The prefrontal cortex may be an important TMS cortical target for managing certain types of pain, including certain neuropathic pain syndromes.